The meaning of life and suffering: A personal task - Santa Cruz Vera, Dalia Jaqueline (2021)
The vulnerability of the human condition expressed in pain, disease and death puts man before the questions of the meaning of life and suffering. The article focuses its interest on the human capacity to give meaning to all situations in life, including that of inevitable suffering. In addition, it proposes some means or educational suggestions to better face these extreme situations of existence: Discover the personal mission of life; develop the virtues of magnanimity, humility and strength; and finally, live life as a gift and service.  It is concluded that filling life with meaning through love and virtue allows suffering to be more easily integrated into life and transformed into an occasion for human growth and personal maturity.